Analysing the effects of solar insolation and temperature on PV cell characteristics. (2021) - Suman,; Sharma, Preetika; Goyal, Parveen
Abstract: Shortage of power, degradation of the environment, and high cost associated with fossil-fuels like coal, natural gas, oil, etc. compel us to find some economical, sustainable and eco-friendly energy sources. Presently, solar energy is gaining worldwide acceptance fora long and is gathering people's attention as it is not only clean, pollution-free but also available on earth without any cost. The usage of solar energy in an efficient way is a big challenge for all researchers. The most commonly used materials for the fabrication of solar cells are mono-crystalline silicon, thin-film technology, polycrystalline silicon and nano-materials. These materials have selected because they are all either in production or have the expectancy of being in production over the next few years. In the present scenario, silicon material based PV cells are dominating the power industry. But in the coming time, nanomaterials such as graphene, carbon nanotubes and many others will be dominating the systems due to their small size and high electrical conductivity. Studying the PV cell characteristics is an important way to know that how a solar cell works and responding to various parameters. This study can be done either through fabrication or mathematical modeling. Hence, in this paper, a single diode solar cell model is chosen and the effect of intensity of solar insolation and temperature is seen. Further, the simulations are being performed to understand the IV and PV characteristics. Finally, the effect of variations in temperature and solar irradiance on electrical parameters such as s/c current, Fill-Factor, o/c voltage, and conversion efficiency have been also discussed.